PENGARUH KEBIJAKAN HUTANG DAN INVESTASI TERHADAP NILAI PERUSAHAAN - Siahaan, Fadjar OP (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
The primary objective of this research is to analyze the effect of Debt to Equity Ratio (DER) and Investment Opportunity Set (IOS on firm value. The data was collected by using pooling method. Sixty-six firms in this research were chosen as a research sample. The statistical method used to test the hyphotesis were multiple regressions, t test, and F test. The empirical result shows that partially all independent (Debt to Equity Ratio/DER and Investment Opportunity Set/IOS) have positive significant effect on firm value. Simultaneously, all independent variable (Debt to Equity Ratio/DER and Investment Opportunity Set/IOS) significantly influenced the firm value. The other finding in this research indicates that IOS has the most significant effect on firm value, then followed by DER.